Studies on breeding market pigs by crossing Duroc with Beltsville No. 1 - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
There has been much discussion in Kansas as to the desirability of cross-breeding inbred breeds (so-called hybrids) with other breeds. Consequently, a Beltsville No.1 (Poland x Landrace origin) was secured and matings planned with the Duroc. The purpose was to study the vigor and size of the litter produced and their ultimate performance in the feedlot as compared with purebred Duroc pigs raised under comparable conditions. In the winter of 1952, nine purebred Duroc sows were mated to a Duroc boar and five Duroc sows were mated to a Beltsville No.1 boar. The following table gives a summary of the results of this experiment.
Keywords: Swine; Duroc; Performance; Rate of gain